(untitled) - Dukkipati, Rao V. (Harrow, 2004)
Discusses in a concise but through manner fundamental statement of the theory, principles and methods of mechanical vibrations. Includes concepts and review of analytical dynamics, the basic single degree of freedom systems and the complex multiple degree of freedom systems the energy and matrix methods, Lagrange’s equations, and an introduction to vibration of continuous systems.
Keywords: Vibration,Động lực học